DEVELOPMENT OF PEDAGOGICAL SKILLS OF STUDENTS OF THE DIRECTION OF HIGHER EDUCATION PRESCHOOL EDUCATION - Muminova Gulasal Baxodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article spoke about the scientific work of an integrative approach to improving the pedagogical abilities of Educators of the preschool educational direction. Social and pedagogical, psychological preparation of the formation of the model of the educator in society – the O’ne in the educational process of the educator.